1989
DOI: 10.1080/02134748.1989.10821599
|View full text |Cite
|
Sign up to set email alerts
|

Autoconcepto de Género y Sistema de Valores

Abstract: El presente trabajo tiene por objeto estudiar los correlatos de valor asociados a los constructos psicológicos de masculinidad y feminidad. Para ello, se han relacionado las puntuaciones obtenidas por una muestra de ambos sexos en las escalas de masculinidad (M), feminidad (F), y masculinidad-femenidad (M-F), del Earlier Personal Attributes Questionnaire, de Spence y Helmreich (1978), con las prioridades establecidas por los mismos sujetos en los valores terminales e instrumentales del Rockeah Value Survey (Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
5
0
5
Order By: Relevance
“…Among the employed, androgynous men and women score higher in all dimensions of perceived employability, yet the difference was significant only for perceived external qualitative employability in comparison to the undifferentiated profile. Androgyny refers to an adaptive personality character structure in which masculine and feminine traits are integrated in a person regardless of their sex (Barberá, 1998). The expression of these traits in an integrated or separate way will depend on the situation (Bem, 1977; Baldwin et al, 1986), which make them more adaptable to different situations.…”
Section: Discussionmentioning
confidence: 99%
“…Among the employed, androgynous men and women score higher in all dimensions of perceived employability, yet the difference was significant only for perceived external qualitative employability in comparison to the undifferentiated profile. Androgyny refers to an adaptive personality character structure in which masculine and feminine traits are integrated in a person regardless of their sex (Barberá, 1998). The expression of these traits in an integrated or separate way will depend on the situation (Bem, 1977; Baldwin et al, 1986), which make them more adaptable to different situations.…”
Section: Discussionmentioning
confidence: 99%
“…This gave rise to what has been called scientific feminism (Sau, 2000) or academic feminism (Bosch & Ferrer, 2003), which seeks to transfer the feminist commitment of articulating society, its laws and norms around a new social contract between men and women, around the construction and transmission of scientific knowledge. This scientific or academic feminism is arranged around what was first called women’s studies and later gender studies or feminist studies (a detailed analysis of what each of these names means can be found in Bonilla, 2010; Bosch & Ferrer, 2003; EIGE, 2018; Ferrer, 2017), whose foundations are precisely the critical contributions from feminism (Barberá, 1998; Flecha, 2010; Meler, 2009; Pilcher & Whelehan, 2010).…”
Section: From Social Feminism To Academic Feminismmentioning
confidence: 99%
“…According to the assumptions and purposes described above, this gender or feminist psychology is framed within academic feminism and fully incorporates the gender or feminist perspective into its undertakings, such that it is characterized by (Barberá, 1998; Ferrer, 2017; Ferrer & Bosch, 2015; Meler, 2009; Unger, 2010): challenging the supposed neutrality of psychological knowledge; questioning the traditional academic and scientific authority and psychological research; spotlighting and questioning the androcentrism underlying certain assumptions in traditional psychology; incorporating the distinction between sex and gender; focusing on analysing the social structures and the sex-gender system; analysing how the lives of women and men are influenced by gender factors (including studying the effects of gender identity, roles and stereotypes and other related issues); and emphasizing improving the lives of women and effecting a social transformation which would remove the existing discriminations and inequalities.…”
Section: Psychology and Gender Or Feminist Social Psychologymentioning
confidence: 99%
See 2 more Smart Citations